New public management as a lever of local governance, a reading in the context of decentralization: case of the city of the of Mbuji-Mayi in DR Congo - TSHIBAND MUSAS , Théodore; KUND KAPEND , Alphonse (Revue Internationale du Chercheur, 2025)
Abstract This article analyzes the challenges of decentralization in the Democratic Republic of Congo, by highlighting new public management as a strategic tool to improve local governance. It identifies several levers to promote local development in particular: political commitment, institutional capacities, training, public-private partnership, civil society and the use of ICT. Indeed, the results of the survey by questionnaire and the semi-structured interview as well as the documentary observation carried out, generally demonstrate that decentralization in the DRC raises several challenges, including, limited citizen participation, regional inequalities, politicization oflocal institutions, skills conflicts, limited institutional capacities as well as the lack of financial resources. As a result, the application of NMP principles such as political commitment, efficiency, efficiency, public-private partnership, civil society, institutional capacities and the use of ICT has an impact on local development.